Revisit Intention to Destination Image, eWOM, and Destination Personality: Kuta Beach Bali, Indonesia - Lestari, Winda (Universitas Mercu Buana, 2021)
Tourism in Bali is magnificent in the eyes of the international world. This beautiful island could attract millions of tourists both foreign and domestic. However, Bali recently has caught both national and international attention due to the huge amount of accumulation of marine litters that were frequently accumulated in the touristic area of the island especially in Kuta Beach Bali. Therefore, in this study, the author did research in regards to know what factors affect tourist’s intention to spend their time in Bali. The objectives of this research are (1) to analyze the influence of destination image towards tourists’ intention to revisit the destination (2) to analyze the influence of eWOM towards tourists’ intention to revisit the destination (3) to analyze the influence of destination personality towards tourists’ intention to revisit the destination. This type of research is quantitative ex post facto. The research sample was 129 tourists who had visited Kuta Beach Bali, Indonesia. Through the path analysis from PLS for version 3.0, it can be concluded that (1) the destination image has a positive and significant positive effect on revisit intention (2) eWOM has a positive and insignificant effect on revisit intention (3) the destination personality has a positive and significant effect on revisit intention. The implication of the results of the research are that efforts must be made to establish the destination reputation through overseeing the waste in tourist sites that could affect the destination itself.